QSAR studies and antimicrobial potential of 1,3-thiazolylphosphonium salts - M. M. Trush; V. V. Kovalishyn; V. M. Blagodatnyi; V. S. Brovarets; S. G. Pilyo; V. M. Prokopenko; D. M. Hodyna; L. O. Metelytsia (The Ukrainian Biochemical Journal, 2016)
The regression QSAR models were built to predict the antimicrobial activity of new thiazole derivatives. Compounds with high predicting activity were synthesized and evaluated against Gram-positive and Gram-negative bacteria and fungi. 1,3-Thiazole-4-ylphosphonium salts 4 and 5 displayed good antibacterial properties and high antifungal activity. The predictions are in a good agreement with the experiment results, which indicate the good predictive power of the created QSAR models.